The equilibrium results analysis in a competing supply chains with consumer returns - Jian Liu; Haiyan Wang (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is, to examine the optimal pricing and ordering strategy of two competing chains with customer returns in Bertrand-Nash game and Stackelberg game, and to investigate in what cases the manufacturer can make more profits from customer returns policy. Design/methodology/approach: We build the customer returns model in the competing chains and compare the equilibrium results in Bertrand-Nash game with that in Stackelberg game. Findings: The main contribution of the present study is the manufacturer can benefit from customer returns policy, only if customer return rate is sufficiently low in two games. In addition, the optimal price, order quantity and profits in Stackelberg game are affected more seriously by customer returns than that in Bertrand-Nash game. Originality/value: The impact of customer returns on the competing chain is initially considered, where the demand is related with the retail price and return price.
Keywords: 650; competing supply chain; consumer returns; Bertrand-Nash game; Stackelberg game